Host–Guest Binding Hierarchy within Redox‐ and Luminescence‐Responsive Supramolecular Self‐Assembly Based on Chalcogenide Clusters and γ‐Cyclodextrin. Issue 51 (30th July 2018) - Ivanov, Anton A.; Falaise, Clément; Abramov, Pavel A.; Shestopalov, Michael A.; Kirakci, Kaplan; Lang, Kamil; Moussawi, Mhamad A.; Sokolov, Maxim N.; Naumov, Nikolay G.; Floquet, Sébastien; Landy, David; Haouas, Mohamed; et al.
Abstract: Water‐soluble salts of anionic [Re6 Q8 (CN)6 ] 4− (Q=S, Se, Te) chalcogenide octahedral rhenium clusters react with γ‐cyclodextrin (γ‐CD) producing a new type of inclusion compounds. Crystal structures determined through single‐crystal X‐ray diffraction analysis revealed supramolecular host–guest assemblies resulting from close encapsulations of the octahedral cluster within two γ‐CDs. Interestingly, nature of the inner Q ligands influences strongly the host–guest conformation. The cluster [Re6 S8 (CN)6 ] 4− interacts preferentially with the primary faces of the γ‐CD while the bulkier clusters [Re6 Se8 (CN)6 ] 4− and [Re6 Te8 (CN)6 ] 4− exhibit specific interactions with the secondary faces of the cyclic host. Furthermore, analysis of the crystal packing reveals additional supramolecular interactions that lead to 2D infinite arrangements with [Re6 S8 (CN)6 ] 4− or to 1D "bamboo‐like" columns with [Re6 Se8 (CN)6 ] 4− and [Re6 Te8 (CN)6 ] 4− species. Solution studies, using multinuclear NMR methods, ESI‐MS and Isothermal titration calorimetry (ITC) corroborates nicely the solid‐state investigations showing that supramolecular pre‐organization is retained in aqueous solution even in diluted conditions. Furthermore, ITC analysis showed that host–guest stability increases significantly ongoing from S to Te. At last, we report herein that deep inclusion alters significantly the intrinsic physical‐chemical properties of the octahedral clusters, allowing redox tuning and near IR luminescence enhancement. Abstract : Supramolecular recognition dictated by chaotropic effect : Water‐soluble [Re6 Q8 (CN)6 ] 4− (Q=S, Se, Te) octahedral clusters react with γ‐cyclodextrin producing supramolecular inclusion systems. The nature of the inner Q ligands influences strongly the water structure‐breaking character of the clusters, resulting in different host–guest stability. The encapsulation modifies significantly the intrinsic physical–chemical properties of the inorganic guest (redox and luminescence).